The Association Between Social Media Use and Adolescent Behavior: A Study at Muhammadiyah 2 Sidoarjo High School - Netty Herawaty; Jumaiyah Jumaiyah; Riyen Imelda; Muhammad Alifza; Zainudin Albar; Dwi Rahmayanti; Lucy Lidiawati Santioso (IJIP : Indonesian Journal of Islamic Psychology, 2025)
This study investigates the association between social media use and adolescent behavior among students at Muhammadiyah 2 Sidoarjo High School, East Java, Indonesia, addressing the limited empirical evidence from faith-based secondary education within urban, peripheral contexts. The research seeks to identify patterns of adolescents’ social media engagement and to examine how variations in usage intensity correspond to behavioral tendencies. A quantitative correlational design was applied, utilizing primary data obtained through an online questionnaire administered to 123 active students from grades X and XI. Descriptive statistics and simple linear regression were employed to evaluate the strength and direction of the relationship between variables. The findings demonstrate a positive and statistically significant directional association (B = 0.255, p < 0.05) between social media use and adolescent behavior, indicating behavioral amplification rather than normative improvement, whereby increased engagement corresponds to more pronounced expressions of both constructive and maladaptive behaviors. Nevertheless, the model’s explanatory power remains modest (Adjusted R² = 12.4%), suggesting that adolescent behavior is predominantly shaped by additional contextual factors, including family environment, religiosity, and peer dynamics. Overall, the results underscore the dual role of social media as a medium for educational engagement and a potential source of behavioral risk, reinforcing the need for structured digital literacy initiatives and guided supervision to foster adaptive online practices among adolescents.